2024
DOI: 10.1128/mbio.03080-23
|View full text |Cite
|
Sign up to set email alerts
|

Candida auris detected in the oral cavity of a dog in Kansas

Theodore C. White,
Brooke D. Esquivel,
Elisa M. Rouse Salcido
et al.

Abstract: Candida auris is an emerging human fungal pathogen, first described in Japan in 2009, and first detected in the United States in 2016. Here, we report the first-ever description of C. auris colonizing a human pet, the first identification of C. auris in a non-human mammal in the United States and the first C. auris isolate from the state of Kansas. While analyzing the oral mycobiome of dogs from a shelter in Kansas, the oral sw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…It has been suggested that birds may have contributed to the global spread of C. auris progenitors, enabling the independent evolution of different clades across continents (Figure 3). The recent discovery of C. auris in the oral cavity of a dog supports the hypothesis of zoonotic transmission [71]. The validation of the theory necessitates multidisciplinary research to clarify transmission dynamics and investigate potential environmental and animal reservoirs.…”
Section: Insights Into the Evolution Of C Aurismentioning
confidence: 89%
“…It has been suggested that birds may have contributed to the global spread of C. auris progenitors, enabling the independent evolution of different clades across continents (Figure 3). The recent discovery of C. auris in the oral cavity of a dog supports the hypothesis of zoonotic transmission [71]. The validation of the theory necessitates multidisciplinary research to clarify transmission dynamics and investigate potential environmental and animal reservoirs.…”
Section: Insights Into the Evolution Of C Aurismentioning
confidence: 89%
“…Candida auris sequences were identified in the ear canal of a Spanish dog with otitis externa and on the skin of two newt species in Cambridgeshire, UK. Subsequent findings extended beyond metabarcoding evidence; live C. auris was isolated from two stray dogs with otitis externa in India ( 13 ) and from the oral cavity of a pet dog in Kansas as documented in the interesting study by White et al ( 14 ).…”
Section: Commentarymentioning
confidence: 92%
“…This instance was the first documented occurrence in Kansas, in an area without previous reports of the pathogen. Notably, despite C. auris’ s known transmission capability and surface survivability, there were no secondary cases in other dogs at the shelter, including the dog’s littermate, even with regular oral contact among dogs and humans ( 14 ). This pattern was also seen in the Indian stray dogs ( 13 ).…”
Section: Commentarymentioning
confidence: 99%
“…Transient oral colonization with this multidrug resistant fungus, in non-human mammals, has already been reported, and the first such case of C. auris oral colonization in a pet was published in 2024. The health implication of this oral colonization in pets is that zoonotic transmission to humans may be possible, given the long period of time that this pathogen can remain on surfaces [ 49 ]. In the case that human transient oral colonization is also reported, screening for oral C. auris may be recommended in the future before dental procedures, due to the possibility of hematogenous spread and even severe systemic infections in immunosuppressed patients.…”
Section: Candida Auris : Multidisciplinary Involvementmentioning
confidence: 99%